Emotion management among displaced middle school students in Khanaqin (Journal of the College of Basic Education, 2022)
It can be said that the agitation administration is leading the individual to a well-established beliefs about its ability to succeed and learn. That the construction of psychological sober administration is balanced Anflat function and take the initiative and perseverance, which relies on the provisions of the individual and behavioral expectations skill and their adequacy to deal successfully with the challenges of the environment for personal gain elevation and ideas glamorous ..The current research also aims to gauge the emotions 1. Department of the displaced students in middle school. 2. Measuring Management feeling among the displaced students, depending on the variable type (males - females). Search and sample consisted of (300) students of displaced people in junior high school in the city of Khanaqin in the academic year (from 22,014 to 2015) was adopted. And Scale (Zubaidi 0.2013) to manage emotions .uand analysis of the data showed the results follows. 1. Find the current sample is characterized by emotions and management Tugod individual differences to the variable type and in favor of male .. it was presented a number of recommendations and suggestions ..